Analysis of Firm Value in Indonesia: The Role of Green Investment, Financial Performance, and Corporate Social Responsibility as Moderation - Ilham Hardi; Dhani Ichsanuddin Nur (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of Green Investment, Profitability, and Leverage on Firm Value with Corporate Social Responsibility (CSR) as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This study uses quantitative methods with moderated regression analysis (MRA) techniques. The population of this study is an energy sector company listed on the Indonesia Stock Exchange as many as 87 companies, and sampling through purposive sampling method resulted in 10 companies. The results showed that Green Investment can contribute to company value, Profitability can contribute to Company Value, and Leverage has no contribution to Company Value. CSR can strengthen the influence of Green Investment on Firm Value, but is unable to moderate the relationship between Profitability on Firm Value, and unable to moderate the relationship between Leverage on Firm Value. This study provides practical implications for companies to continue to strengthen sustainable investment and Corporate Social Responsibility (CSR) transparency to increase firm value.